Associations between NK Cells in Different Immune Organs and Cellular SIV DNA and RNA in Regional HLADR− CD4+ T Cells in Chronically SIVmac239-Infected, Treatment-Naïve Rhesus Macaques - Xinjie Li; Liyan Zhu; Yue Yin; Xueying Fan; Linting Lv; Yuqi Zhang; Yijin Pan; Yangxuanyu Yan; Hua Liang; Jing Xue; Tao Shen (Viruses, 2022)
With the development of NK cell-directed therapeutic strategies, the actual effect of NK cells on the cellular SIV DNA levels of the virus in SIV-infected macaques in vivo remains unclear. In this study, five chronically SIVmac239-infected, treatment-naïve rhesus macaques were euthanized, and the blood, spleen, pararectal/paracolonic lymph nodes (PaLNs), and axillary lymph nodes (ALNs) were collected. The distributional, phenotypic, and functional profiles of NK cells were detected by flow cytometry. The highest frequency of NK cells was found in PBMC, followed by the spleen, while only 0~0.5% were found in LNs. Peripheral NK cells also exhibited higher cytotoxic potential (CD56− CD16+ NK subsets) and IFN-γ-producing capacity but low PD-1 and Tim-3 levels than those in the spleen and LNs. Our results demonstrated a significant positive correlation between the frequency of NK cells and the ratios of cellular SIV DNA/RNA in HLADR− CD4+ T cells (r = 0.6806, p < 0.001) in SIV-infected macaques, despite no discrepancies in the cellular SIV DNA or RNA levels that were found among the blood, spleen, and LNs. These findings showed a profile of NK cell frequencies and NK cytotoxicity levels in different immune organs from chronically SIVmac239-infected, treatment-naïve rhesus macaques. It was suggested that NK cell frequencies could be closely related to SIV DNA/RNA levels, which could affect the transcriptional activity of SIV proviruses. However, the cytotoxicity effect of NK cells on the latent SIV viral load in LNs could be limited due to the sparse abundance of NK cells in LNs. The development of NK cell-directed treatment approaches aiming for HIV clearance remains challenging.